The Scaling and Modeling of Pay and the Robustness of the Effect of Core Self Evaluations on Career Success - Ganzach, Yoav; Pazy, Asya (Frontiers in Psychology, 2021)
A number of recent studies used nominal pay in estimating the effects of individual differences, particularly core-self-evaluation, on career success. We show that this practice may lead to results that are substantively different from the results when the logarithm of pay is used. We conduct three constructive replications of previous studies, and argue that substantive conclusion based on the results of nominal pay are misleading.